Concentration and time dependent cytotoxic effect of methanolic crude extracts of pseuduvaria macrophylla on the human cancer cell line - Aziz, A.; Zulkiflee, A.B.; Yusof, F.Z.M. (2017)
The previous study demonstrated promising anti-cancer potential in methanolic crude extracts using single concentration, especially on breast cancer cells under 24 hours treatment. The present study investigates the effective concentration of bark and leaf methanolic extract on MCF-7 breast cancer cell line under 48 and 72 hours of treatment. The method employed was MTT assay to determine the half maximal inhibitory concentration (IC50) of both extracts at different concentration under 48 & 72 hours of treatment. The IC50 was obtained by plotting the concentration (μg/mL) versus the percentage of inhibition of each extract. The MCF7 cell line had decreased response to both extracts within 72 hours but showing promising cytotoxicity within 48 hours especially for leaf methanolic extracts at concentration of 140 μg/mL ± 0.23 to inhibit 50% of tested cancer cell line, meanwhile the medium inhibitory concentration (IC50) of bark methanolic extract on MCF7 cells was 242 μg/mL ± 0.13. The results showed that the the IC50 of leaf methanolic extracts was comparably lower than the IC50 of bark methanolic extracts. In fact, leaf methanolic extracts demonstrated better efficacy on the MCF7 after been treated within 48 hours compared to 72 hours. In other words, leaf methanolic extract more potent than bark methanolic extracts.